Rhodian Influence at Kalynda during the Hellenistic Period: Analysis of Oil Lamps from Asar Tepe Excavations (Şerefler/Dalaman) - Hakan Gerçek (Gephyra)
This study delves into the oil lamp fragments recovered during the 2022-2023 excavation season at Kalynda. Despite not being found in their entirety, the current state of these lamps allows for the determination of their forms. Originating from Rhodes in the 3rd century BC during the Hellenistic Period, these oil lamps were encountered in various regions, particularly through maritime trade.Rhodes, a prominent trading center in the 3rd century BC, held a leading position in maritime trade, actively engaging with the Mediterranean, islands, Egypt, and the Levant. The strong presence of Rhodes in maritime trade facilitated the widespread distribution of goods produced on the island to major trade centers across this geographical expanse. The discovery of Rhodian goods, including oil lamps, in Kalynda—a settlement situated between Lycia and Caria—underscores the city's integral role in trade. The political dominance of Rhodes in Lycia and Caria during the Hellenistic Period further contributed to an influx of Rhodian products in regional cities like Kalynda. Beyond the oil lamps, Rhodian influence in the city is notably reflected in amphora handles bearing Rhodian stamps. The lamps discussed in this study not only enrich our understanding of imported common wares in Kalynda but also illuminate the expansive trade network orchestrated by Rhodes during the Hellenistic Period.